Managing Differentiated Learning Process in Implementing Emancipated Curriculum at Thailand - Indonesian School - Shelly Andari; Karwanto Karwanto; Ainur Rifqi; Ahmad Wicaksono; Khairul Azhar Jamaludin; Mohd Hanafi; Syunu Trihantoyo (Indonesia Approach Education, 2024)
The policy of Emancipated curriculum is implemented to accelerate the achievement of the national education goals. Moreover, this curriculum is not only implemented in Indonesia but also in Indonesian Schools which located abroad. The focus of this research is directed towards (a) differentiated learning planning at the Indonesian School in Bangkok (SIB), Thailand; (b) implementation of differentiated learning at the SIB, Thailand; and (c) evaluation of differentiated learning at the SIB, Thailand. This study conducted three data collection techniques, including: (1) interviews; (2) documentation; and (3) observation. The data were then processed using NVivo 12. The result of this research is that the learning in the SIB, Thailand is designed by taking into account the developmental stages and the current level of achievement of students. It is aligned with the learning needs and reflects the diverse characteristics and development of students, making the learning meaningful and enjoyable. Moreover, SIB Thailand highly prioritizes future-oriented and sustainable learning.